2006
DOI: 10.1242/jcs.03247
|View full text |Cite
|
Sign up to set email alerts
|

Actin regulation in endocytosis

Abstract: Actin in yeast and the mechanism of endocytosisActively growing budding yeast contains three distinct actin structures that are visible by fluorescence microscopy of Rhodamine-phalloidin-stained cells: cortical actin patches, which are now thought to represent sites of endocytosis; actin cables, which are crucial for polarity and for movement of exocytic vesicles; and a contractile actin ring, which plays a role in cytokinesis (Adams and Pringle, 1984).The first evidence linking actin to the endocytic process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
148
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(159 citation statements)
references
References 126 publications
6
148
0
1
Order By: Relevance
“…Our data, limited to the detailed analysis of a few cells, suggest that this process seems to be essential in the internalization of 35 and 15 nm AuNPs, however LTR was not able to block uptake in the case of the 5 nm AuNPs. Some studies have shown that mammalian cells, contrary to non mammalian cells, can show endocytosis even in the presence of LTR 24,25 . They are able to perform internalization by clathrin coated pits, albeit at a reduced rate.…”
Section: Discussionmentioning
confidence: 99%
“…Our data, limited to the detailed analysis of a few cells, suggest that this process seems to be essential in the internalization of 35 and 15 nm AuNPs, however LTR was not able to block uptake in the case of the 5 nm AuNPs. Some studies have shown that mammalian cells, contrary to non mammalian cells, can show endocytosis even in the presence of LTR 24,25 . They are able to perform internalization by clathrin coated pits, albeit at a reduced rate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, actin filaments play a role in regulating the size of endocytic invaginations from the plasma membrane. In yeast, growing actin filaments are proposed to elongate endocytic regions of the plasma membrane in preparation for the formation of endocytic vesicles (Smythe and Ayscough, 2006;Yarar et al, 2005). The presence of long actin filaments surrounding these endocytic invaginations indirectly produces structural size limitations.…”
Section: The Role(s) Of Actin In Cytostome Structure and Regulationmentioning
confidence: 99%
“…Because of the similarities between the current model for hemoglobin transport and the endocytic pathway in higher eukaryotes (Goldberg et al, 1990;Hoppe et al, 2004;Langreth et al, 1978;Saliba et al, 2003), we investigated the role of actin dynamics in hemoglobin transport to the FV. Actin has been shown to play various regulatory roles in endocytosis, including recruiting endocytic components to the plasma membrane, initiating plasma membrane invaginations, vesicle scission and transport to endocytic compartments (Kaksonen et al, 2006;Qualmann et al, 2000;Smythe and Ayscough, 2006). As intermediate filaments have not been identified in P. falciparum and microtubules do not appear until the schizont stage (Taraschi et al, 1998), well after the majority of hemoglobin internalization and degradation has occurred, we hypothesized that actin may play a role in cytostome formation and hemoglobin transport to the FV.…”
mentioning
confidence: 99%
“…Endocytosis is required for recycling of plasma membrane lipids and trafficking proteins, and for uptake or down-regulation of cell surface receptors (reviewed in Smythe and Ayscough, 2006). In yeast, a requirement for a dynamic actin cytoskeleton at sites of endocytosis has been recognized for many years (Kü bler and Riezman, 1993;Raths et al, 1993).…”
Section: Introductionmentioning
confidence: 99%